2011
DOI: 10.1016/j.jneb.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Rural and Urban Differences in the Associations between Characteristics of the Community Food Environment and Fruit and Vegetable Intake

Abstract: INTRODUCTIONThe consumption of fruits and vegetables (FV) is a key indicator of a healthy diet associated with positive health outcomes such as the reduction in incidence of cardiovascular disease and cancer.1 , 2 The 2005 Dietary Guidelines for Americans call for 4.5 cups (9 servings) of FV daily based on a 2,000 calorie level.3 This compares unfavorably to a nationwide assessment of total FV consumption that indicates mean per-capita consumption of FV is roughly 2.6 cups, not accounting for losses resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
154
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(161 citation statements)
references
References 44 publications
6
154
0
1
Order By: Relevance
“…The intervention group came from the center of Veendam (a small city with around 20,000 inhabitants), but the control group came from several smaller villages in a more rural area. Dean and Sharkey (2011) have shown that fruit and vegetable consumption depends on different factors in rural and urban environments. In their study, they suggest that food security and distance to food sources play a larger role in rural settings, as compared with urban settings (Dean & Sharkey, 2011).…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention group came from the center of Veendam (a small city with around 20,000 inhabitants), but the control group came from several smaller villages in a more rural area. Dean and Sharkey (2011) have shown that fruit and vegetable consumption depends on different factors in rural and urban environments. In their study, they suggest that food security and distance to food sources play a larger role in rural settings, as compared with urban settings (Dean & Sharkey, 2011).…”
Section: Main Findingsmentioning
confidence: 99%
“…Dean and Sharkey (2011) have shown that fruit and vegetable consumption depends on different factors in rural and urban environments. In their study, they suggest that food security and distance to food sources play a larger role in rural settings, as compared with urban settings (Dean & Sharkey, 2011). Also, possibly more people in rural areas cultivate their own fruits and vegetables.…”
Section: Main Findingsmentioning
confidence: 99%
“…9 6) 1.00 6) 0.82 6) 95.5 ± 2. 1.00 6) 0.64 6) 100.0 ± 0.0 89.4 ± 2.1 1.00 ± 0.00 0.71 ± 0.05 Snacks 97.0 6) 93.9 6) 0.89 6) 0.86 6) 97 Fat and oils 95.5 ± 2.1 93.9 6) 0.85 ± 0.12 0.88 6) 94.7 ± 2.9 97.0 ± 0.0 0.82 ± 0.14 0.94 ± 0.00 P value 0.0027 7) 0.0095 7) 0.0081 8) 0.0290 8) 1) Only for 12 food subgroups(except vegetables, fruits, fish and shellfish) which have both general food and food with healthy option. 2) Agreement of inter-observer, n = number of food store 3) Agreement of intra-observer, n = number of food store 4) Food with healthy option: whole grains and processed foods with healthy option such as low sodium, low sugar, low fat, low calorie, no fat, calcium enriched, food for weight management, decaffeinated coffee, cold-chain juice, see ' Table 3 …”
Section: 대상 식품상점 선정mentioning
confidence: 97%
“…70 The overall effect is to create pockets with minimal proximal food access, where residents must either pay higher prices at gas stations, convenience stores, or small grocers or have access to a vehicle and the time required to reach a major grocery outlet, 71 which is a major barrier for low-income households. 72,73 In addition, work from Sharkey et al 74 shows that Texas residents in more deprived neighborhoods and rural areas must travel farther to reach a supercenter, 75 although in Louisiana, income level is not associated with supercenter locations. 41 Kaufman 76 showed that, across the United States, low-income and urban populations have lower access to both supermarkets and supercenters.…”
Section: Supercenters Socioeconomic Status and Disparities In Accesmentioning
confidence: 99%